IMPLEMENTASI KOMUNIKASI VERTIKAL DALAM ORGANISASI : (STUDI DESKRIPTIF PENERAPAN DOWNWARD DAN UPWARD COMMUNICATION DI BAGIAN PROTOKOL DAN KOMUNIKASI PIMPINAN SEKRETARIAT DAERAH KABUPATEN LOMBOK UTARA) - Sandi Putra; Raden Abdul Rasyid; I Made Putra Suryantara; Lalu Ahmad Rahmat (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2023)
ABSTRACT his research examines the implementation of vertical communication within the organization through the application of downward communication and upward communication in the Communication Protocol Section of the Regional Secretariat Leaders of North Lombok Regency. This research includes qualitative research with a phenomenological study approach. Analyze the data by organizing the data and breaking it down into units, synthesizing, selecting what is important, and making conclusions. The results of this study indicate that communication from top to bottom is carried out through the practice of oral communication between superiors and subordinates as well as written communication through social media and letters. Keywords: Vertical Communication, Protocol, Leadership Communication.